HEALTH PROMOTION FOR WOMEN IN THE CLIMACTERIC PERIOD WITHIN PRIMARY CARE (CIPEEX, 2025)
The climacteric is the transition between a woman's fertile and infertile periods, marked by hormonal changes that impact physical, mental, and social well-being. Within primary care, there are protocols and manuals developed by the Ministry of Health of Brazil, with the aim of offering support to these women during the climacteric. This research aims to identify challenges women face during the climacteric. An exploratory, longitudinal, and descriptive field study with a qualitative approach was conducted with 30 women aged 40 to 55 at the Center for Comprehensive Women's Health Care in Anápolis, GO. The results revealed gaps in health education beyond menopause, including the presentation of symptoms, discussion of hormonal and non-pharmacological treatments, and education on quality of life and sexuality. Additionally, the study found that symptomatology and lifestyle significantly influence quality of life during the climacteric. It concludes that welcoming and actively listening to women in this age group, alongside a multidisciplinary approach within primary care units, fosters self-knowledge and supports women in seeking a dignified life during this transition. Thus, this research can serve as an aid for the planning and maintenance of manuals and improvement of care for this population.
Keywords: womens health; climacteric; health promotion